Heterozygous SOD2 deletion selectively impairs SERCA function in the soleus of female mice. Issue 10 (17th May 2022) - Braun, Jessica L.; Messner, Holt N.; Cleverdon, Riley E. G.; Baranowski, Ryan W.; Hamstra, Sophie I.; Geromella, Mia S.; Stuart, Jeffrey A.; Fajardo, Val A.
Abstract: The sarco(endo)plasmic reticulum Ca 2+ ATPase (SERCA) restores intracellular Ca 2+ ([Ca 2+ ]i ) to resting levels after muscle contraction, ultimately eliciting relaxation. SERCA pumps are highly susceptible to tyrosine (T)‐nitration, impairing their ability to take up Ca 2+ resulting in reduced muscle function and increased [Ca 2+ ]i and cellular damage. The mitochondrial antioxidant enzyme, superoxide dismutase 2 (SOD2), converts superoxide radicals into less reactive H2 O2 . Heterozygous deletion of SOD2 ( Sod2 +/− ) in mice increases mitochondrial oxidative stress; however, the consequences of reduced SOD2 expression in skeletal and cardiac muscle, specifically the effect on SERCA pumps, has yet to be investigated. We obtained soleus, extensor digitorum longus (EDL), and left ventricle (LV) muscles from 6 to 7 month‐old wild‐type (WT) and Sod2 +/− female C57BL/6J mice. Ca 2+ ‐dependent SERCA activity assays were performed to assess SERCA function. Western blotting was conducted to examine the protein content of SERCA, phospholamban, and sarcolipin; and immunoprecipitation experiments were done to assess SERCA2a‐ and SERCA1a‐specific T‐nitration. Heterozygous SOD2 deletion did not alter SERCA1a or SERCA2a expression in the soleus or LV but reduced SERCA2a in the EDL compared with WT, though this was not statistically significant. Soleus muscles from Sod2 +/− mice showed a significant reduction in SERCA's apparent affinity for Ca 2+ when compared to WT, corresponding with significantly elevated SERCA2a T‐nitration in the soleus. No effect was seen in the EDL or the LV. This is the first study to investigate the effects of SOD2 deficiency on muscle SERCA function and shows that it selectively impairs SERCA function in the soleus.